Implementation of Individual Candidate Reviews in the Election of Mayor in Surakarta City - Murti Samadi, Wibowo; Rukmi B, Shinta (Wacana Hukum, 2022)
This study aims to further examine the implementation of individual candidate reviews in the mayoral election in Surakarta City in 2020. The city of Surakarta implemented direct elections in 2020 which were followed by political parties, in this case PDI Perjuangan (Gibran Rakabuming Raka and the individual Teguh Prakoso). ) and individual candidate Bagyo Suparjo who will appear in the direct election according to the decision of the Pilwalkot participants.This study uses a normative legal research method using a statutory approach (Statute Approach) and a case approach (Case Approach). The approach in normative research examines data that is directly taken from a literature review and secondary data that can be studied through document studies is found at the Surakarta City Regional General Election Commission. This is in accordance with the 1945 Constitution and Law no. 10 of 2016. This approach is expected to get an overview of normative studies using descriptive analysis and purposive sampling.The results of the temporary study showed that the implementation of the individual candidate review in the mayoral election in the city of Surakarta was won by Gibran Rakabuming Raka and Teguh Prakoso who defeated Bagyo Suparjo. The existence of individual candidates in the political and democratic system occurs because Law Number 32 of 2004 concerning Regional Government only limits and facilitates candidates for regional heads who come from political parties only. Individual candidates in the post-conflict local elections in Indonesia are not significant because one of the regulations governing individual candidates is burdensome to individual candidates, even though individual candidates have been regulated in the 1945 Constitution and strengthened by the Constitutional Court Decision Number 5/PUU-V/2007 which is the political right of the people to vote. Chosenas a form of democracy and human rights. Deparpolization is caused by the decline in public confidence in political parties so that people look for other political routes and provide space for people who do not have political vehicles, which are expected to be able to answer the deadlock of political parties so that their political rights can run well.